Synthesis and characterization of activated carbon from Agarwood (Aquilaria malaccensis) for xenoestrogen treatment - Sahib, Mosa Jafer (2020)
The incidence of water contamination by endocrine-disrupting chemicals (EDCs),xenoestrogen such as bisphenol-A (BPA) and estradiol (EST) is increasing in recentdecades. This study was aimed to synthesize and characterize activate carbon derived fromagarwood (agar AC) for xenoestrogen adsorption. The synthesis was conducted byphysicochemical activation using sulfuric acid which was employed as an activator at 180oC activation temperature followed by calcination under nitrogen condition. Both BPA andEST were detected in six selected rivers and lakes in Malaysia. Agar AC was characterizedby electron microscopy, X-ray diffraction, micro-Raman, Fourier transform infraredspectroscopy, and Zeta potentials to determine which mechanism produced optimal resultfor the adsorption of BPA and EST. The carbon porosity was determined by nitrogenadsorption-desorption isotherm at 77K using Brunauer-Emmett-Teller (BET) method. Theprepared agar AC was mainly micro and mesoporous in nature with BET surface area 1092m2/g. Optimization results showed an optimum removal of BPA was 86% (at carbon dosage1wt.%, pH 7, contact time of 180 minutes and temperature of 50 C) and EST removal was79% (at pH 11, carbon dosage 4 wt.%). Experimental data were fitted into the Langmuirand Freundlich adsorption isotherm models. Both Langmuir and Freundlich isothermspredicted BPA adsorption of agar AC at R2 values greater than 0.99, signifyingchemisorption and physio-sorption processes. The Freundlich isotherm gives a betteramount of EST uptake onto prepared activated carbon, indicating heterogeneouschemisorption process. In conclusion, the adsorption capacity of prepared agar AC showedhigh adsorption capacity (BPA 439 mg/g, EST 1664 mg/g) compared with the commercialAC. The implication of this study provides green adsorption with high sorption capacitymaterial that can be applied for the removal of BPA and EST from water bodies such asrivers and lakes.